1996
DOI: 10.1088/1355-5111/8/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Antiphase dynamics in pump-modulated multimode intracavity second-harmonic generation

Abstract: Abstract. We determine numerically the response of a multimode laser with intracavity secondharmonic generation to a periodic modulation of the gain in the linear and nonlinear regimes.We show that resonances can appear either at the relaxation oscillation frequency or the low internal frequency and at its first subharmonic. Instabilities leading to period doubling occur at the low internal frequency and at its first harmonic.Multimode lasers have been shown to display diverse behaviours, regular and irregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…3. As it can be seen, for small nonlinearity, ǫ < 0.8 × 10 −4 , there is a rather good agreement between theoretically [Wang & Mandel, 1993] and numerically obtained results. However, when nonlinearity increases, 0.8 × 10 −4 < ǫ < 1.0 × 10 −4 , the minimal number of modes obtained in numerial simulations 5 is larger than the number predicted theoretically.…”
Section: Simplified Model -No Spatial-hole Buring Effectsupporting
confidence: 75%
See 1 more Smart Citation
“…3. As it can be seen, for small nonlinearity, ǫ < 0.8 × 10 −4 , there is a rather good agreement between theoretically [Wang & Mandel, 1993] and numerically obtained results. However, when nonlinearity increases, 0.8 × 10 −4 < ǫ < 1.0 × 10 −4 , the minimal number of modes obtained in numerial simulations 5 is larger than the number predicted theoretically.…”
Section: Simplified Model -No Spatial-hole Buring Effectsupporting
confidence: 75%
“…The results presented in [James et al, 1990b, Magni et al, 1993, where the crosssaturation coefficient was assummed to be constant for all modes, are compared with the numerical data. It is shown that the theoretically obtained [Wang & Mandel, 1993] linear dependence of the minimal number of modes necassary for stabilization the laser output on the strength of nonlinearity agrees with the numerical solutions only in the case of sufficiently small nonlinearity. For larger values of nonlinearity, due to the cancellation of modes during the evolution, the minimal number of modes obtained by the numerical simulations is larger than the number which follows from the theoretical predictions.…”
Section: Introductionmentioning
confidence: 64%
“…When the pump-modulation frequency is far from 2 1 (not 2 ) the response is linear in the sense that the laser is tied to the pump modulation and displays inphased P1 solutions. The nonlinear response is observed near 2 1 . Within the range limited by the points labelled 1 and 2, the lasers oscillate at half the modulation frequency (i.e.…”
Section: Medium-amplitude Pump Modulationmentioning
confidence: 92%
“…In a recent paper [1], we analysed numerically the response of a multimode laser, with intracavity second harmonic generation (ISHG), to a periodic modulation of the gain in the linear and nonlinear regimes. We found that, depending on the relative phase of the modal gain modulation, the resonance which is expected at the relaxation oscillation frequency can appear to be or can be shifted to the lower internal frequency.…”
mentioning
confidence: 99%
See 1 more Smart Citation